1989
DOI: 10.1128/mcb.9.9.3685
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, sequence, and expression of a human keratin K5 gene: transcriptional regulation of keratins and insights into pairwise control.

Abstract: The mitotically active basal layers of most stratified squamous epithelia express 10 to 30% of their total protein as keratin. The two keratins specifically expressed in these cells are the type II keratin K5 (58 kilodaltons) and its corresponding partner, type I keratin K14 (50 kilodaltons), both of which are essential for the formation of 8-nm filaments. Dissecting the molecular mechanisms underlying the coordinate regulation of the two keratins is an important first step in understanding epidermal different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
3

Year Published

1993
1993
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 53 publications
4
96
3
Order By: Relevance
“…In fact, staining for plectin revealed an almost complete colocalization with K14. The persistence of K14 is at odds with previous data showing that the stability of a keratin in cell culture is dependent on the expression of its partner keratin (Kulesh and Oshima, 1988;Kulesh et al, 1989;Lersch et al, 1989; Magin et al, 1990;Bader et al, 1991).To ascertain the expression of K14, we performed Northern and Western blots. Northern blot analysis of total RNA revealed that the K14 mRNA expression was unaffected in the absence of one wild-type allele of K5 but decreased in K5-deficient mice (Figure 2).…”
mentioning
confidence: 40%
See 1 more Smart Citation
“…In fact, staining for plectin revealed an almost complete colocalization with K14. The persistence of K14 is at odds with previous data showing that the stability of a keratin in cell culture is dependent on the expression of its partner keratin (Kulesh and Oshima, 1988;Kulesh et al, 1989;Lersch et al, 1989; Magin et al, 1990;Bader et al, 1991).To ascertain the expression of K14, we performed Northern and Western blots. Northern blot analysis of total RNA revealed that the K14 mRNA expression was unaffected in the absence of one wild-type allele of K5 but decreased in K5-deficient mice (Figure 2).…”
mentioning
confidence: 40%
“…Previous data had shown that the stability of a keratin depended on the expression of its partner keratin (Kulesh et al, 1989;Lersch et al, 1989). Yet, the immunofluorescence analysis had revealed the persistence of K14 expression in K5 Ϫ/Ϫ mice.…”
Section: Biochemical Analysis Of Keratin Complexesmentioning
confidence: 99%
“…6). It was surprising that the levels of K5 were appreciable in the -/-mouse sample, since the stability of a type II keratin is known to be dependent upon its partner (Kulesh and Oshima, 1988;Lersch et al, 1989). In previous studies on the putative K14 null EBS patients, several mechanisms were proposed to account for the stabilization of K5 (Chan et al, 1994;Rugg et al, 1994).…”
Section: K15 Is a Natural Partner For K5 And These Keratins Constitutmentioning
confidence: 99%
“…Cell culture studies have indicated that K5 is degraded in the absence of K14 (Kulesh and Oshima, 1988;Lersch et al, 1989;Chan et al, 1994). In epidermis, however, the reduction in K5 protein was not as dramatic as might have been expected based on the paucity of filaments in the basal layer of K14 -/ -epidermis (Rugg et al, 1994; present study).…”
Section: A New Basal Keratin In the Picture: New Insights Into Diseasmentioning
confidence: 99%
See 1 more Smart Citation